2007
DOI: 10.1124/jpet.107.121772
|View full text |Cite
|
Sign up to set email alerts
|

High-Dose Acetaminophen Inhibits the Lethal Effect of Doxorubicin in HepG2 Cells: The Role of P-glycoprotein and Mitogen-Activated Protein Kinase p44/42 Pathway

Abstract: Doxorubicin (DOX) is a widely used chemotherapeutic drug for human hepatocellular carcinoma (HCC). A major limitation to its effectiveness is the development of multidrug resistance of cancer cells. In clinical trials, patients with advanced HCC were treated with high-dose acetaminophen (HAAP) in an effort to improve the antitumor activity of chemotherapeutics. In this study, we investigated the effect of concomitant treatment of DOX and HAAP on hepatoma-derived HepG2 cells. Viability, cell cycle distribution,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 38 publications
1
27
0
Order By: Relevance
“…DNA damaging agents besides DOX, such as etoposide, ionizing radiation, and ultraviolet irradiation also demonstrated similar effects on ERK activation [18,22]. The role of sustained ERK activation in causing cell cycle arrest and apoptosis was confirmed by adding PD98059 or U0126 to DOX and showing that the DOX effects were attenuated by inhibiting MEK-ERK activation in HepG2 and other cell types [18,19,22]. In contrast, we observed that the U0126/DOX combination was more effective at inhibiting cell growth and inducing apoptosis than the single agents in HepG2 cells.…”
Section: Discussionmentioning
confidence: 65%
“…DNA damaging agents besides DOX, such as etoposide, ionizing radiation, and ultraviolet irradiation also demonstrated similar effects on ERK activation [18,22]. The role of sustained ERK activation in causing cell cycle arrest and apoptosis was confirmed by adding PD98059 or U0126 to DOX and showing that the DOX effects were attenuated by inhibiting MEK-ERK activation in HepG2 and other cell types [18,19,22]. In contrast, we observed that the U0126/DOX combination was more effective at inhibiting cell growth and inducing apoptosis than the single agents in HepG2 cells.…”
Section: Discussionmentioning
confidence: 65%
“…In addition, APAP can enhance the chemotherapeutic anticancer effects of drugs used to treat neuroblastoma, leukemia and ovarian carcinoma (30,34,35). According to the above studies, APAP can activate different cytotoxic mechanisms in liver, kidney and tumor cells (14,19,21,31,36). To date, most studies have focused on the mechanisms of APAP-induced cytotoxicity and on how to prevent high-dose APAP-related poisoning of the liver and the kidneys.…”
Section: Introductionmentioning
confidence: 97%
“…A major limitation to its effect is the development of multi drug resistance of cancer cells [8]. Histopathological changes such as necrosis, hepatocyte degeneration, sinusoidal dilatation, haemorrhage and vascular congestion and dilatation also occur [9].…”
mentioning
confidence: 99%